Exploring Liminal Spaces in Older Age: Navigating the Enduring State of Dual Sensory Impairment (DSI) - Moira E. Dunsmore; Julie Schneider; Heather McKenzie; James A. Gillespie (SAGE Open)
Dual sensory impairment (DSI), a combination of vision and hearing loss, presents significant social and physical challenges to older adults and their social networks. Despite its growing global prevalence, DSI is underexplored in extant literature and receives little attention in health policy or ageing research. This qualitative study explores the social experiences of older adults with DSI in Australia. Using data from 15 ( n  = 15) intensive interviews with older adults, this study applies constructivist Grounded Theory (GT) methodology to examine the social experiences of older persons with DSI. This study conceptualizes the social experiences of DSI as an “enduring state,” representing the ongoing social effort involved in the daily life work of DSI. These findings suggest that a socially inclusive and interdisciplinary approach to future service, research and practice has capacity to bridge the social gap that currently exists in health and social care for the older DSI family.